MO872: Relationship Between Vitamin D Levels And SARS-COV-2 Infection in Dialysis Patients. (3rd May 2022) - Marín Delgado, Carlos; F. Navarro-González, Juan; Del Castillo Rodríguez, Nieves; Gallego, Eduardo; Siverio Morales, Orlando; Toribio Muñoz Pacheco, Ameth; Cecilia Urzola Rodríguez, Giomar; Macia, Manuel
Abstract: BACKGROUND AND AIMS: Hypovitaminosis D is highly prevalent in patients with Chronic Kidney Disease (CKD). This is considered a consequence of a decreased renal mass and a reduction in the number of proximal tubular cells, which absorb the filtered native vitamin D and then be hydroxylated to its active form by 1α-hydroxylase. Hypovitaminosis D is defined as serum levels of 25-hydroxy-vitamin D3 lower than 30 ng/mL. The decrease in vitamin D causes bone and mineral abnormalities and can also play a role in various pathologies, such as cardiovascular disease, insulin resistance, diabetes, autoimmune diseases and infections. Clinical practice guidelines recommend treating hypovitaminosis D. The role of vitamin D in acute respiratory tract infections and other viral infections has been widely studied. It has an immunomodulatory role due to the expression of the enzyme 1α-hydroxylase by the epithelium of the respiratory tract, dendritic cells and lymphocytes, which is essential for the activation of vitamin D in the lungs. In this way, an influence is created on the lung capacity to fight infections and respond to allergic stimuli. Vitamin D has the potential to influence the severity and outcomes of COVID-19. In fact, several studies have established a consistent relationship between hypovitaminosis D and the severity of COVID-19. We have a population of dialysis patients with a tendency to hypovitaminosis D and, on the other hand, an influence of hypovitaminosis D in respiratory infections such as SARS-CoV-2 infection. Thus, we consider it interesting to study whether the incidence of hypovitaminosis D is higher in dialysis patients with SARS-CoV-2 infection than in those who do not. METHOD: An observational, analytical, ambispective, multicentre study was carried out under normal clinical practice conditions. The study subjects are patients on haemodialysis program of the province of Santa Cruz de Tenerife, in the period between January 2021 and January 2022. As variables we selected age, sex, personal history, haemodialysis time, serum levels of 25-hydroxy-vitD3, treatment with native vitamin D, presence of SARS-CoV-2 infection diagnosed by RT-PCR in nasopharyngeal swab, vaccination. The information collected is organized in a database of the SPSS Statistics v22 program. For quantitative variables, the comparison between groups is made by means of an analysis with the Student's t -test for independent samples. Qualitative variables are analyzed using the Chi-squared test or Fisher's exact test. All data were analyzed using the SPSS Statistics v22 program. The level of significance is established for a value of P  < 0.05. RESULTS: A total of 60 haemodialysis patients were included, 36 men (60%) and 24 women (40%). The mean age was 64 years. The most common cause of kidney disease was diabetic nephropathy (35%). The median time on dialysis was 24.5 months. 73.3% of the patients presented hypovitaminosis D and 35% received treatment with vitamin D. 23 patients had SARS-CoV-2 infection (38.3%). 2 patients (3.3%) died of COVID-19. There were no significant differences between the two comparison groups (patients with and without SARS-CoV-2 infection) in relation to sex, age, cause of kidney disease, diabetes, time on dialysis, vitamin D intake. We also did not observe significant differences in relation to vitamin D levels or the presence of hypovitaminosis D. There are significant differences in relation to vaccination (p 0.00). 39.1% of the patients with SARS-CoV-2 infection were not vaccinated. 90% of all unvaccinated patients had SARS-CoV-2 infection. 97.3% of the uninfected patients were vaccinated. CONCLUSION: Hypovitaminosis D is very common in CKD patients on dialysis, however, despite its immunomodulatory role, we did not find a higher incidence of hypovitaminosis D in dialysis patients with SARS-CoV-2 infection. In our series, we have not found factors associated with SARS-CoV-2 infection in dialysis patients, with the exception of vaccination. Therefore, vaccination in our dialysis patients is being essential to prevent a higher number of cases of SARS-CoV-2 infection.